2022
DOI: 10.1002/lno.12288
|View full text |Cite
|
Sign up to set email alerts
|

High ebullitive, millennial‐aged greenhouse gas emissions from thermokarst expansion of peatland lakes in boreal western Canada

Abstract: Methane (CH4) and carbon dioxide (CO2) emissions from small peatland lakes may be highly sensitive to climate warming and thermokarst expansion caused by permafrost thaw. We studied effects of thermokarst expansion on ebullitive CH4 and CO2 fluxes and diffusive CH4 fluxes from a peatland thaw lake in boreal western Canada. Ebullitive CH4 fluxes from the thaw edge (236 ± 61 mg CH4 m−2 d−1) were double and quadruple that of the stable lake edge and center, respectively. Modeled diffusive CH4 fluxes did not diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 98 publications
0
2
1
Order By: Relevance
“…In our study, four of five ponds had minor N 2 O uptake similar to the peatland stages. We also found no differences in N 2 O exchange between thermokarst and stable edges, despite previous studies on these ponds found higher CH 4 emissions from thermokarst edges (Kuhn et al, 2022), suggesting different controls on CH 4 and N 2 O emissions in boreal ponds.…”
Section: Greenhouse Gas Balance Of Peatland Pondscontrasting
confidence: 85%
See 2 more Smart Citations
“…In our study, four of five ponds had minor N 2 O uptake similar to the peatland stages. We also found no differences in N 2 O exchange between thermokarst and stable edges, despite previous studies on these ponds found higher CH 4 emissions from thermokarst edges (Kuhn et al, 2022), suggesting different controls on CH 4 and N 2 O emissions in boreal ponds.…”
Section: Greenhouse Gas Balance Of Peatland Pondscontrasting
confidence: 85%
“…Boreal peatland ponds have been identified as potential hot spots for N 2 O, CH 4 , and CO 2 emissions (Huttunen et al., 2002; Kortelainen et al., 2020; Kuhn et al., 2021) with thermokarst activity enhancing CH 4 and CO 2 emissions (Kuhn et al., 2022). In our study, four of five ponds had minor N 2 O uptake similar to the peatland stages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation